The Agricultural Labor Market: Farmer Perception and the Influence on The Efficiency of Rice Farming - Mamilianti, Wenny; Huda, Miftahul; Asmara, Rosihan; Bakhtiar, Ary (Journal of Ecohumanism, 2024)
Therefore, this research aims to analyze the factors that influence the farmer’s perspective regarding the labor provider service and the effect of the service that is used by the farmers on the technical efficiency level. This research uses the methodology that involves the utilization of logit regression analysis to test the cross-sectional data that was obtained from 200 farmers in Ngawi, Lumajang, Pasuruan, Malang in Indonesia as a sample. The measurement of technical efficiency uses the Cobb-Douglas production function with the Stochastic Production Frontier approach and the Tobit Regression model to determine the effect of labor provider business on technical efficiency. This research found that factors that influence the farmer’s perception of the labor provider are age, land area, the worker’s wage, and the use of agricultural tools. The technical efficiency level can certainly still be improved by addressing the influencing factors, namely the use of information technology, agricultural mechanization, and the positive response towards the organizations that help in the availability of input, such as the labor provider service. The findings in this research provide an overview of how a farmer should perceive the agricultural labor provider service, especially in agriculture in the industrial or high labor wages areas.